2017
DOI: 10.3847/1538-4357/aa6f5f
|View full text |Cite
|
Sign up to set email alerts
|

Evidence for Different Disk Mass Distributions between Early- and Late-type Be Stars in the BeSOS Survey

Abstract: The circumstellar disk density distributions for a sample of 63 Be southern stars from the BeSOS survey were found by modelling their Hα emission line profiles. These disk densities were used to compute disk masses and disk angular momenta for the sample. Average values for the disk mass are 3.4×10 −9 and 9.5×10 −10 M ⋆ for early (B0-B3) and late (B4-B9) spectral types, respectively. We also find that the range of disk angular momentum relative to the star are between 150-200 and 100-150 J ⋆ /M ⋆ , again for e… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
51
0
11

Year Published

2017
2017
2021
2021

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(70 citation statements)
references
References 53 publications
(88 reference statements)
8
51
0
11
Order By: Relevance
“…Moreover, statistical results were based on a percentage of the representative models (best range of models) for each Hα emission line, where they found that the disk mass and angular momentum distributions are different between early (B0-B3) and late (B4-B9) subspectral types. Also, they found values of the power-law density distribution (see eq.1 on Arcos et al (2017)) of log ρ ∼ -10.4 to -10.2, and n ∼ 2.0 to 2.5 and disk masses of 3.4×10 −9 and 9.5×10 −10 M for early and late spectral types, respectively. For the disk size, they calculated the emitting region containing 90% of the total Hα flux given a range of values concentrated between 10 and 15 stellar radius.…”
Section: Physical Models Fitted On Hα Emission Linesmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, statistical results were based on a percentage of the representative models (best range of models) for each Hα emission line, where they found that the disk mass and angular momentum distributions are different between early (B0-B3) and late (B4-B9) subspectral types. Also, they found values of the power-law density distribution (see eq.1 on Arcos et al (2017)) of log ρ ∼ -10.4 to -10.2, and n ∼ 2.0 to 2.5 and disk masses of 3.4×10 −9 and 9.5×10 −10 M for early and late spectral types, respectively. For the disk size, they calculated the emitting region containing 90% of the total Hα flux given a range of values concentrated between 10 and 15 stellar radius.…”
Section: Physical Models Fitted On Hα Emission Linesmentioning
confidence: 99%
“…It is important to note that our actual photometric analysis does not fit the infrared excess. The reader is invited to use radiative transfer codes such as Hdust (Carciofi 2001) to reproduce the IR excess as well as physical models of Be stars (e.g., Domiciano de Souza et al 2014;Silaj et al 2016;Arcos et al 2017).…”
Section: Photometrymentioning
confidence: 99%
See 1 more Smart Citation
“…Other studies have determined the radial extent of the Hα emitting region for sets of Be stars and specific stars. For example, using Hα spectroscopy Hanuschik (1986) find the emitting regions of 20 R * for 24 bright Be stars, Slettebak et al (1992) determine sizes of 7 to 19 for a sample of 41 Be stars, and more recently Arcos et al (2016) find a concentration of disk sizes of 5 to 20 R * . Size estimates based on interferometric GD models encompassing 80% of a star's brightness at FWHM for Hα emitting regions for 12 Be stars are shown in Rivinius et al (2013).…”
Section: Discussion and Summarymentioning
confidence: 99%
“…Carciofi (2011) used the VDD model to construct the basis of new paradigm for the interpretation of Be stars observations. Then, it was widely used to successfully model Be stars Silaj et al, 2010;Touhami et al, 2011;Carciofi et al, 2012;Klement et al, 2015;Vieira et al, 2015;Faes et al, 2016;Arcos et al, 2017;Jones et al, 2017;Klement et al, 2017;Vieira et al, 2017;Marr et al, 2018;Rímulo et al, 2018). More details about the VDD model can be found in Sect.…”
Section: The Disks Of Be Starsmentioning
confidence: 99%